2022
DOI: 10.30892/gtg.43311-905
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Long-Run Relationship Between Tourist Arrivals and Economic Growth in Nepal? An Empirical Assessment Based on Ardl Bounds Test Approach

Abstract: The tourism industry has become a significant economic contributor to a number of countries worldwide. Until COVID-19, tourism was the world's largest and fastest-growing business. The importance of tourist arrivals and the examination of their effects has triggered curiosity among different researchers, as tourism helps in balance of payment and boosts the overall GDP of the nation. Thus, this paper aimed to examine the long-run relationship among the number of tourist arrivals per year and economic growth (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In this study, the short-term from a long-term perspective has not been distinguished. The results of the study conducted in developing countries showed that tourist arrivals had a positive impact on economic growth in the long term, but not in the short run (Khanal & Khanal, 2022).…”
Section: Resultsmentioning
confidence: 97%
“…In this study, the short-term from a long-term perspective has not been distinguished. The results of the study conducted in developing countries showed that tourist arrivals had a positive impact on economic growth in the long term, but not in the short run (Khanal & Khanal, 2022).…”
Section: Resultsmentioning
confidence: 97%
“…Subymon (2018) utilizes qualitative analysis to scrutinize the socio-cultural impacts of tourism on Nepalese host communities, offering insights into the evolving cultural dynamics shaped by tourism. Khanal and Khanal (2020) employ an ARDL bounds test with data from World Development Indicators to reveal that a 1 percent increase in tourist arrivals corresponds to a substantial 1.15 percent increase in Nepal's GDP. This quantitative approach offers a precise measurement of the economic impact of tourism in the country.…”
Section: Literature Reviewmentioning
confidence: 99%